A Social-Political Content Analysis of Syrian Migrants’ Reports Prior and Subsequent to the Death of Alan Kurdi - lebbal, anfal; hamane, soraya (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2021)
The present research is an attempt to investigate whether an observable change of discourse in British press’ articles –in which the tragedy of Alan Kurdi’s death had been discussed– is existent. The tragic death of the three-year-old Syrian boy whose lifeless body was found washed up on a Turkish shore on September 2nd, 2015 was reported through world-wide media. And even though the reports all tread on sympathetic and compassionate grounds, the difference and change that this research aims to capture within newspapers’ social-political discourse is that reoccurring within the scope of before and after Alan’s death. Through applying Fairclough’s analysis method, this research is dedicated to collect data and analyze British newspapers’ articles through description, input tables, lexical analysis, and an overview of linguistic changes, all in order to further demonstrate the way media is used not only to report, but to influence and manipulate the audience’s perceptions.